Adherence to Antiplatelet Medications among Persistent and Non-Persistent Older Patients with Peripheral Arterial Disease - Wawruch Martin; Murin Jan; Tesar Tomas; Paduchova Martina; Petrova Miriam; Celovska Denisa; Matalova Petra; Havelkova Beata; Trnka Michal; Aarnio Emma (MDPI, 2022)
Secondary prevention of peripheral arterial disease (PAD) includes administration of antiplatelet agents, and adherence to medication is a requirement for an effective treatment. The aim of this study was to analyse adherence measured using the proportion of days covered (PDC) index separately in persistent and non-persistent patients, and to identify patient- and medication-related characteristics associated with non-adherence in these patient groups. The study cohort of 9178 patients aged >= 65 years in whom PAD was diagnosed in 1/-12/2012 included 6146 persistent and 3032 non-persistent patients. Non-adherence was identified as PDC < 80%. Characteristics associated with non-adherence were determined using the binary logistic regression model. In the group of persistent patients, 15.3% of subjects were identified as non-adherent, while among non-persistent patients, 26.9% of subjects were non-adherent to antiplatelet medication. Administration of dual antiplatelet therapy (aspirin and clopidogrel) and a general practitioner as index prescriber were associated with adherence in both patient groups. Our study revealed a relatively high proportion of adherent patients not only in the group of persistent patients but also in the group of non-persistent patients before discontinuation. These results indicate that most non-persistent PAD patients discontinue antiplatelet treatment rapidly after a certain period of adherence.